PENGARUH KONSERVATISME DALAM LAPORAN KEUANGAN TERHADAP EARNINGS RESPONSE COEFFICIENT - PUJIATI, LILIK (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
Earning information that generated in the conservatism financial statemen areconsidered to have benefits for the investor to predict the reaction of financialstatement reporting. This study aims to determine the effect of conservatism in thefinancial statements of the earnings response coefficient (ERC) as well as to determinethe effect of good corporate governance (GCG) on the relationship betweenconservatism in financial statements with the earnings response coefficient (ERC). Thedata used in this study is a secondary data obtained from the Indonesia StockExchange and of the Indonesian Capital Market Directory (ICMD). To determine theeffect of conservatism and good corporate governance in the financial statements of theearnings response coefficient is used multiple linear regression.Based on the results of simultaneous tests using the F test is known that theoverall conservatism of the independent variables, good corporate governance, andfirm size simultaneously have significant effect on the earnings response coefficient.This suggests that the results of this study support the hypothesis that has beenpresented. Based on the results of the partial test using t test between each independentvariable conservatism, good corporate governance, and firm size on earnings responsecoefficient is known that the variable conservatism, good corporate governance, andfirm size partially have significant effect on the earnings response coefficient (ERC) .This suggests that the results of this study support the hypothesis that has beenpresented.Cause of the results of this study show the influence of conservatism onearnings response coeficient then conservatism is still relevant for use by the issuer inthe presentation of information in financial statements.Keywords: conservatism, earnings response coefficient, good corporate governance